Incomplete markets with no Hart points - Robert M. Anderson; Roberto C. Raimondo (Theoretical Economics, 2007)
We provide a geometric test of whether a general equilibrium incomplete markets (GEI) economy has Hart points—points at which the rank of the securities payoff matrix drops. Condition (H) says that, at each nonterminal node, there is an affine set (of appropriate dimension) that intersects all of a well-specified set of convex polyhedra. If the economy has Hart points, then Condition (H) is satisfied; consequently, if condition (H) fails, the economy has no Hart points. The shapes of the convex polyhedra are determined by the number of physical goods and the dividends of the securities, but are independent of the endowments and preferences of the agents. Condition (H) fails, and thus there are no Hart points, in interesting classes of economies with only short-lived securities, including economies obtained by discretizing an economy with a continuum of states and sufficiently diverse payoffs.
Keywords: D52; 330; Incomplete Markets; GEI model; Hart points